Applying climate-smart agriculture technologies to smallholder farms in Kenya: farmers' manual - Haggai, Ndukhu; Mutuma, Evans; Muraya, Moses; Gathungu, Geofrey; Nderitu, Peris; Opetu, Grace; Kahindi, Roseline; Kosgei, Geoffrey; Waswa, Boaz Shaban; Templer, Noel; Kinyua, Ivy Wambui; Nderi, Alex; et al. (2023)
This guide is here to help smallholder farmers deal with the challenges of climate change and make their farms more resilient. By going through this manual, we want to not only assist farmers in adapting to climate change but also enhance their food security and livelihoods. The goal is to build farming households that can withstand the impacts of a changing climate